PwC's Sports Survey 2018 (PwC, 2018)
This survey was conducted by our Sports Business Advisory team between the months of May and June 2018 through an online questionnaire that was distributed to sports industry leaders across the world. Sharing our vision of establishing an independent perspective on the state of the industry, a number of high-profile sports executives supported us by sharing the questionnaire with their peers. This helped us ensure broader representation across regions and industry segments. PwC`s global network further supported us to ensure greater participation, particularly in Asia. In total, we received 470 responses to our questionnaire across 42 counties. As participants did not always provide responses to all questions, we have included the precise number of responses received for the questions that are graphically represented within this report. The analysis in this report is primarily based on the collective opinion of the respondents. It is complemented by data provided to us by Intelligent Research in Sponsoring GmbH, a leading independent international sports marketing research agency in Germany, as well as desktop research